Investigation of acquired dysfibrinogenaemia in adult patients with sepsis using fibrinogen function vs. concentration ratios: a cross-sectional study - Toenges, Rosa; Steiner, Michael; Weber, Christian Friedrich; Miesbach, Wolfgang (Frontiers in Medicine, 2023)
Inherited or acquired molecular abnormalities form a clinically heterogeneous group of fibrinogen disorders called dysfibrinogenaemia. Apart from a pediatric case report and in contrast to other clinical conditions, acquired dysfibrinogenaemia has not been previously reported in septic patients. In an observational cohort study, 79 adult septic patients were investigated for the presence of acquired dysfibrinogenaemia at the time of their admission to the intensive care unit (ICU) of the University Hospital Frankfurt. Following established recommendations, fibrinogen clotting activity versus antigen ratios were analyzed using Clauss fibrinogen, prothrombin-derived fibrinogen, and radial immunodiffusion (RID) fibrinogen concentration. Prothrombin-derived fibrinogen levels were highest (527 ± 182 mg/dL) followed by Clauss fibrinogen (492 ± 209 mg/dL) and radial immunodiffusion fibrinogen (426 ± 159 mg/dL). Very few cases demonstrated hypofibrinogenaemia making overt disseminated intravascular coagulation (DIC) unlikely in the cohort investigated. Clauss/RID fibrinogen ratios were lower (1.17 ± 0.19) compared to prothrombin time-derived/RID ratios (1.35 ± 0.33). Using the Clauss/RID dataset, 21 % of patients (16/76 patients) demonstrated values below a threshold ratio for suspected acquired dysfibrinogenaemia arbitrarily set at 1.0. In contrast, prothrombin-derived ratios were below the threshold in only 7 % (4/58 patients). The results point to the presence of acquired dysfibrinogenaemia in part of adult septic patients. If confirmed in further studies, this may form part of a specific laboratory signature of a sepsis-associated coagulation phenotype.